Clinical and sociodemographic aspects of inflammatory bowel disease patients - Meenakshi Gururani; Joshi SC; Arun Joshi; Aishwary Bajpai (Asian Journal of Medical Sciences, 2025)
Background: Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), is a chronic gastrointestinal condition with rising prevalence in India. The Kumaon region of Uttarakhand faces an increasing burden of IBD, yet data on its clinical and sociodemographic characteristics remain scarce. This study aims to explore these aspects to improve diagnosis, treatment, and outcomes in this under-researched population. Aims and Objectives: The study aimed to investigate the clinical and sociodemographic characteristics of IBD patients in the Kumaon region. Key objectives included identifying disease patterns, clinical features, complications, and treatment practices to enhance understanding and management of IBD. Materials and Methods: This cross-sectional, observational study was conducted from December 2022 to June 2023 at a tertiary care center. Fifty histologically confirmed IBD patients were included. Data on demographic details, clinical presentation, laboratory findings, and treatment were collected and analyzed using SPSS. Results: A slight female predominance (52%) was observed, with a mean age of 39.38 years. UC was the predominant subtype (86%), with CD accounting for 12%. Key symptoms included diarrhea (98%), rectal bleeding (52%), and abdominal pain (48%). Anemia was prevalent in 70%, and 36% had extraintestinal manifestations. Treatment was mainly mesalamine (96%) and glucocorticoids (52%), with limited use of biologics (2%). Conclusion: IBD poses a significant health burden in Kumaon, with UC being the predominant subtype. Early diagnosis, comprehensive treatment, and improved access to advanced therapies are essential to address this growing concern.